2020
DOI: 10.1007/s00167-020-06138-7
|View full text |Cite
|
Sign up to set email alerts
|

The forgotten joint score-12 is a valid and responsive outcome tool for measuring success following hip arthroscopy for femoroacetabular impingement syndrome

Abstract: Purpose The forgotten joint score-12 (FJS-12) is an outcome questionnaire designed to evaluate joint awareness. The responsiveness and validity of the English language version of the FJS-12 in patients undergoing hip arthroscopy for femoroacetabular impingement (FAI) is not known. Methods Consecutive patients undergoing hip arthroscopy for a diagnosis of FAI were prospectively followed up over a 1 year period. Patients completed preoperative and postoperative FJS-12, EuroQol 5 Dimension (EQ-5D-5L), and the 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Ingelsrud et al reported an MCID of the FJS-12 in TKA between 14 and 23 points [ 27 ]. Robinson et al assessed the MCID of 15 points for FJS-12 in total hip arthroplasty [ 34 ]. Behrend et al calculated an FJS-12′s MCID of 13 in anterior cruciate ligament reconstruction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ingelsrud et al reported an MCID of the FJS-12 in TKA between 14 and 23 points [ 27 ]. Robinson et al assessed the MCID of 15 points for FJS-12 in total hip arthroplasty [ 34 ]. Behrend et al calculated an FJS-12′s MCID of 13 in anterior cruciate ligament reconstruction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also for this reason that this outcome tool is effective in distinguishing good from excellent performers after hip arthroscopy and why it has been recommended for young, active patients. 8 Other outcome tools used to assess hip arthroscopy have demonstrated significant ceiling effects with an inability to distinguish good from excellent outcomes. 33 Our results here present a PASS score in the lower half of possible scores on the 0-100 scale of the FJS-12, suggesting that while not a sports-specific score, the FJS-12 may be useful in assessing high-performing patients.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data included age, gender, body mass index (BMI), and Scottish Index of Multiple Deprivation (SIMD) vingtile ranking (social deprivation index). 30 Patients completed preoperative FJS-12, 8 , 10 iHOT-12, 31 Tegner and EQ-5D-5L 32 questionnaires 2 weeks before surgery at the pre-assessment clinic and at a minimum of one year postoperatively. Plain anteroposterior radiographs were used to assess for cam and/or pincer lesions as well as to calculate the lateral center edge angle (LCEA), and assess Tönnis classification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations